Pengenalan Inovasi PELITA Sebagai Upaya Percepatan Cakupan Dokumen Akta Kematian di Desa Plumbungan Kabupaten Sragen - Merlin Swantamalo Magna; Ulfah Sulistyowati; Yuliana Ristantya Ningsih (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Although death certificates are indispensable for a myriad of legal and administrative processes, public cognizance of their significance remains limited. To rectify this, the Sragen Regency's Population and Civil Registration Office has introduced PELITA (Pelaporan Kematian Langsung Terbit Akta), a groundbreaking initiative designed to streamline and expedite the issuance of death certificates. The Diploma IV Program in Demography and Civil Registration Studies at Sebelas Maret University facilitated a socialization campaign in Plumbungan Village to disseminate information about PELITA. A comprehensive approach involving planning, implementation, and evaluation was adopted to foster public comprehension of the procedures and advantages associated with death certificates. The campaign yielded positive results, evincing a heightened public awareness of the importance of death certificates and appreciation for PELITA's user-friendly services. These findings underscore PELITA's potential to augment the coverage of death certificate ownership and, consequently, enhance the overall quality of civil registration services at the village level.